ENVIRONMENTAL ISSUES IN YANUSA NUGROHO'S SHORT STORIES 'BUKIT MAWAR', 'BLARAK', AND 'NYANYIAN KLARAS' - Winarti; Aris Hidayatulloh; Sholiyah; Intan Rachma Firdaus (Leksema: Jurnal Bahasa dan Sastra, 2025)
This study is driven by the escalating global ecological crisis resulting from natural resource exploitation and industrialization, alongside prevailing perceptions that literary studies lack relevance in addressing real-world challenges, particularly environmental issues. To emphasize the contribution of literature in building ecological awareness, this study analyzes the three short stories by Yanusa Nugroho, namely Bukit Mawar, Blarak, and Nyanyian Klaras, which describe the interaction between humans and nature as well as criticism of environmental damage. The objective of this study is to reveal the representation of the ecological crises and the messages of environmental conservation in the three short stories by Yanusa Nugroho. This study applies Greg Garrard’s ecocriticism theory, which highlights major themes such as wilderness, apocalypse, pastoral, dwelling, and The Earth, with a qualitative descriptive method based on text analysis. Data was obtained through literature study and analyzed to identify symbols, narratives, and local wisdom that reflect the relationship between humans and nature. The results show that the ecological crisis is not only physical damage, but also involves social and cultural dimensions. The three short stories emphasize the importance of ecological ethics by caring for the landscape, maintaining the natural cycle, and respecting the earth as a life system.